2015
DOI: 10.12693/aphyspola.127.1282
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-C2S Synthesis from Fly Ash of Fluidize-Bed Boiler for CO2Capture

Abstract: This paper describes the CO2 capture performance of cement blended paste incorporating gamma-dicalcium silicate (gamma-C2S) made with industrial by-products, by taking into consideration of eect of CaCO3, y ash replacement ratio under the sintering process. X-ray diraction method was conducted in order to quantitatively investigate the gamma-C2S content. CO2 capture performance of mortar sample incorporating gamma-C2S was investigated by means of compressive strength test using accelerated carbonation chamber.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Both ( and ) dicalcium silicate phases form during clinker manufacture, when the material is burnt at 550 °C. The lower reactivity of the -C2S phase would explain its unchanging proportion in the total mineralogy of all the cements analysed, even after 15 years [53].…”
Section: Discussionmentioning
confidence: 98%
“…Both ( and ) dicalcium silicate phases form during clinker manufacture, when the material is burnt at 550 °C. The lower reactivity of the -C2S phase would explain its unchanging proportion in the total mineralogy of all the cements analysed, even after 15 years [53].…”
Section: Discussionmentioning
confidence: 98%
“…Figure 1 shows the results of X-ray diffraction analysis of each material used in this study. As a result of the X-ray diffraction analysis, peaks of CaO, CaSO 4 and Fe 2 O 3 were detected in the CFBA2, and an amorphous peak and peak of anhydrite were detected in the BFS. In addition, peaks of CaO, Calcite, Anhydrite, and Quartz minerals were confirmed in DGS.…”
Section: Methodsmentioning
confidence: 99%
“…The Fe and Mg ions in olivine can be substituted by Ca ions without destroying the symmetry of the crystal. The olivine Ca 2 SiO 4 that belongs to the orthorhombic crystal system is also one of the polymorphs of belite (β-Ca 2 SiO 4 ), known as γ-dicalcium silicate (γ-Ca 2 SiO 4 ) (Naa et al, 2015). Previous studies have shown that among common olivine minerals, γ-Ca 2 SiO 4 has a significantly dominant surface water absorption capacity (Kerisit et al, 2013), suggesting the potentially high carbonation reactivity.…”
Section: Introductionmentioning
confidence: 99%